On Certain Subclass of Analytic Functions - Khan, Nazar; Noor, Khalida Inayat; Khan, Nasir; Ahmad, Qazi Zahoor; Chung, Yao Liang (Armenian Journal of Mathematics, 2022)
In the present investigation, a new general subclass $M_{α ,β }\left( φ \right) $ of analytic functions is defined. Some subordination relations, inclusion relations, integral preserving properties, convolution properties and some other interesting properties are studied.